Who benefits from transfers? - Samuel Hoey; Thomas Peeters; Francesco Principe (Tinbergen Institute, 2020)
One major argument to legitimize the transfer system in European club football is that transfer fees paid by hiring clubs result in a redistribution of revenues from large market to small market clubs, which may lead to more intense on-field competition. We investigate this claim using a unique dataset of digitalized financial accounts for a representative sample of clubs across eight national football associations. Overall, the transfer system leads to a very modest reduction in revenue inequality. Small market clubs rarely earn substantial amounts of money from the transfer market. The main financial beneficiaries are clubs around the middle of the market size distribution. A select group of large market clubs makes significant transfer losses, but this does not undo these clubsâ exteuro™ initial financial advantage.
Keywords: L41; J41; K12; L83; 330; labor contracts; transfer system; European football; antitrust; revenue redistribution